A high-rate long-life energy storage cell, a battery device, a power utilization device, and an energy storage device
Patent Information
- Application Number
- CN202512017324.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-30
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-12-30
AI Technical Summary
然而在上述场景对于器件的运行工况有着特殊的要求,如电力自动化备电需要储能器件具有长的浮充寿命和高的放电倍率,电力调频电源要求储能器件具备大倍率充放电特性和长循环寿命,现有磷酸铁锂电池面临寿命短倍率性能差等问题,为满足寿命和功率要求,充放电过程需要在较浅的SOC(充电状态)/DOD(放电深度)进行,在能量上需要冗余配置,但是会增加成本,同时具有较大的安全隐患
本发明通过正极双面涂层厚度与集流体厚度比、涂层压实密度与真密度比、导电剂含量、NP比等关键参数的精准协同设计,从根本上解决了现有磷酸铁锂电池大倍率充放电容量衰减快、循环寿命短的问题。本发明储能单体在25℃环境下,5C恒流充入比≥82%,最高达90%,5C放电倍率≥85%,最高达92%,远超现有磷酸铁锂电池5C充入比≤70%、放电倍率≤75%的水平;在5C倍率下循环10000次后,容量保持率仍≥85%,最高达93%,较现有技术循环10000次后容量保持率≤70%的表现实现质的提升,完全满足电力调频、制动能量回收等场景对高功率、长寿命的严苛需求。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery cell technology, and in particular to a high-rate, long-life energy storage cell, battery device, power consumption device, and energy storage device. Background Technology
[0002] The existing power system is characterized by two highs: a significant increase in the proportion of renewable energy on the source side and a significant increase in the electrification level on the load side. However, new energy sources are characterized by randomness, volatility, and intermittency. The increase in electrification makes it more difficult to predict power on the load side, which will exacerbate the source-load mismatch problem and thus affect the stability of grid frequency and voltage.
[0003] To ensure the safety and reliability of the power grid, the existing power system is adding more power monitoring devices. These devices can monitor the operation of power generation, transmission, transformation, and distribution in real time, and collect, integrate, analyze, and mine the data through network systems. This enables local and remote control, monitoring, and management of power, improving the efficiency and quality of power distribution. Simultaneously, large-scale energy storage devices are deployed at the source and load sides to regulate power quality, such as peak shaving and valley filling, frequency regulation and voltage stabilization, smoothing the output of new energy sources, and enhancing the ability of new energy storage to support the stable operation of the power system. Energy storage devices, as backup or main power sources for these devices, play a crucial supporting role in ensuring their reliable operation.
[0004] Electrochemical energy storage is widely used in power systems due to its high energy density, good power characteristics, fast response speed, and good environmental adaptability. Among them, lithium iron phosphate (LFP) batteries are the primary choice in power systems because of their good safety and long lifespan. However, the above-mentioned scenarios place special requirements on the operating conditions of the devices. For example, power automation backup requires energy storage devices to have long float charge lifespan and high discharge rate, while power frequency regulation power supplies require energy storage devices to have high charge and discharge rate characteristics and long cycle life. Existing LFP batteries face problems such as short lifespan and poor rate performance. To meet the lifespan and power requirements, the charging and discharging process needs to be carried out at a relatively shallow SOC (State of Charge) / DOD (Depth of Discharge), requiring redundant energy configuration, but this increases costs and poses significant safety risks. Summary of the Invention
[0005] To address the aforementioned defects and shortcomings in existing technologies, and considering the requirements of practical scenarios, a new energy storage cell with long cycle life and high rate capability is proposed. This cell exhibits significantly superior rate capability and long cycle life compared to existing lithium iron phosphate batteries, effectively meeting the demands of power frequency regulation for novel energy storage devices.
[0006] One of the objectives of this invention is to provide a high-rate, long-life energy storage cell, including an electrode assembly and an electrolyte; The electrode assembly includes a positive electrode, a separator, and a negative electrode stacked sequentially. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector; The parameters of the positive electrode active material layer after rolling meet the following: The ratio of the total thickness of the double-sided coating of the positive electrode active material layer to the thickness of the positive electrode current collector is 2.5-4.5; The ratio of the compaction density of the coating of the positive electrode active material layer to the true density of the active material in the positive electrode active material layer is 0.55-0.65; The mass of the conductive agent in the positive electrode active material layer accounts for 5%-10% of the total mass of the positive electrode active material layer; The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector; The ratio of the theoretical capacity of the positive electrode to the theoretical capacity of the negative electrode is 1.1-1.2.
[0007] The parameters of the negative electrode active material layer after rolling meet the following: The ratio of the total thickness of the double-sided coating of the negative electrode active material layer to the thickness of the negative electrode current collector is 4.0-7.5; The ratio of the compaction density of the coating of the negative electrode active material layer to the true density of the active material in the negative electrode active material layer is 0.60-0.72; The mass of the conductive agent in the negative electrode active material layer accounts for 2%-5% of the total mass of the negative electrode active material layer.
[0008] Preferably, the active material of the positive electrode active material layer includes one or more of ternary materials, lithium iron phosphate, or lithium cobalt oxide; The active material of the negative electrode active material layer includes one or more of graphite, hard carbon, or soft carbon.
[0009] Preferably, the separator membrane comprises one or more of polypropylene, polyethylene, polyethylene / polypropylene copolymer, or cellulose.
[0010] The thickness of the isolation membrane is 20-40 μm; The ratio of the porosity to the thickness of the isolation membrane is 0.02-0.022.
[0011] Preferably, the areal density of the positive electrode active material layer is 8-12 mg / cm³. 2 The areal density of the negative electrode active material layer on one side is 3.5-4.5 mg / cm³. 2 .
[0012] Preferably, the conductive agent includes one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, or porous carbon.
[0013] Preferably, the positive current collector includes one or more of conventional aluminum foil, carbon-coated aluminum foil, or porous aluminum foil; The negative electrode current collector includes one or more of the following: plain copper foil, carbon-coated copper foil, or porous copper foil.
[0014] Preferably, the electrolyte comprises a solvent, additives, and an electrolyte; The solvent includes one or more of methyl ethyl carbonate, diethyl carbonate, ethylene carbonate, ethyl acetate, propyl acetate, or ethyl propionate. Electrolyte additives include one or more of vinylene carbonate, fluoroethylene carbonate, or 1,3-propane sulpholactone. The amount of electrolyte additive added shall not exceed 2.5% of the total mass of the electrolyte; The electrolyte is lithium hexafluorophosphate, and the concentration of lithium hexafluorophosphate is 1-1.2 mol / L.
[0015] The second objective of this invention is to provide a battery device comprising, as described above, a high-rate, long-life energy storage cell, wherein the battery device is at least one of a battery module, a battery pack, or an energy storage battery.
[0016] A third objective of this invention is to provide an electrical device, including the battery device described above.
[0017] The fourth objective of this invention is to provide an energy storage device, including the battery device as described above, wherein the battery device is used to store electrical energy.
[0018] The beneficial effects of this invention are: This invention fundamentally solves the problems of rapid capacity decay and short cycle life of existing lithium iron phosphate batteries at high charge and discharge rates by precisely coordinating key parameters such as the ratio of positive electrode double-sided coating thickness to current collector thickness, coating compaction density to true density ratio, conductive agent content, and NP ratio. The energy storage cell of this invention, under 25℃ conditions, exhibits a 5C constant current charge ratio ≥82%, reaching a maximum of 90%, and a 5C discharge rate ≥85%, reaching a maximum of 92%, far exceeding the existing lithium iron phosphate battery levels of ≤70% 5C charge ratio and ≤75% discharge rate. After 10,000 cycles at 5C, the capacity retention rate remains ≥85%, reaching a maximum of 93%, representing a qualitative improvement over the existing technology's ≤70% capacity retention rate after 10,000 cycles. This fully meets the stringent requirements for high power and long lifespan in scenarios such as power frequency regulation and regenerative braking.
[0019] This invention optimizes high rate capability and long lifespan while controlling the positive electrode surface density to 8-12 mg / cm³.2 The surface density of the negative electrode is 3.5-4.5 mg / cm³. 2 The ratio of current collector to coating ensures that the energy density of the energy storage unit reaches 95-115Wh / kg, meeting the basic energy storage requirements in practical applications and avoiding the problem of sacrificing energy density simply to pursue rate or lifespan.
[0020] The energy storage unit of this invention can quickly respond to grid frequency regulation and operate stably even after dozens of cycles per day. It can be directly adapted to various scenarios such as power frequency regulation, braking energy recovery, and AGV robots. Detailed Implementation
[0021] The present application will now be described in further detail with reference to embodiments. In the following description, certain specific details are included to provide a comprehensive understanding of the various disclosed embodiments. However, those skilled in the art will recognize that embodiments can be implemented without employing one or more of these specific details, but using other methods, components, materials, etc. Unless otherwise required by the present invention, the terms "comprising" and "including" should be interpreted in an open-ended, inclusive sense, meaning "including but not limited to". Throughout this specification, "an embodiment," "an embodiment," "a preferred embodiment," or "some embodiments" means that at least one embodiment includes a specific reference element, structure, or feature related to that embodiment. Therefore, the phrases "in an embodiment," "in an embodiment," "in a preferred embodiment," or "in some embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. Furthermore, specific elements, structures, or features may be combined in one or more embodiments in any suitable manner.
[0022] According to a first aspect of the present invention, a high-rate, long-life energy storage cell is provided, comprising an electrode assembly and an electrolyte; The electrode assembly includes a positive electrode, a separator, and a negative electrode stacked sequentially. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector; The parameters of the positive electrode active material layer after rolling meet the following: The ratio of the total thickness of the double-sided coating of the positive electrode active material layer to the thickness of the positive electrode current collector is 2.5-4.5; The ratio of the compaction density of the coating of the positive electrode active material layer to the true density of the active material in the positive electrode active material layer is 0.55-0.65; The mass of the conductive agent in the positive electrode active material layer accounts for 5%-10% of the total mass of the positive electrode active material layer; The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector; The ratio of the theoretical capacity of the positive electrode to the theoretical capacity of the negative electrode is 1.1-1.2.
[0023] The parameters of the negative electrode active material layer after rolling meet the following: The ratio of the total thickness of the double-sided coating of the negative electrode active material layer to the thickness of the negative electrode current collector is 4.0-7.5; The ratio of the compaction density of the coating of the negative electrode active material layer to the true density of the active material in the negative electrode active material layer is 0.60-0.72; The mass of the conductive agent in the negative electrode active material layer accounts for 2%-5% of the total mass of the negative electrode active material layer.
[0024] In this invention, the true density of the active material in the positive electrode active material layer is the theoretical density of the positive electrode active material crystal, expressed as ρ. c It is expressed as: the true density of the active material in the negative electrode active material layer is the theoretical density of the negative electrode active material crystal, expressed as ρ. a express; In this invention, the total double-sided coating thickness of the positive electrode active material layer after roll forming is denoted by t. c The thickness of the positive electrode current collector is expressed in t. Al express, t c With t Al The ratio of lithium ions to ion concentration (LID) is 2.5-4.5. A ratio less than 2.5 results in a high proportion of current collector components, reducing the content of active materials, lowering energy density, and rendering the material impractical. A ratio greater than 4.5 leads to an excessively thick coating, resulting in rapid electron conduction in the current collector and slow ion migration within the thick coating. This severe imbalance between electron and ion velocities makes it difficult to match the electron conductivity of the current collector with the conduction of ions in the electrode, leading to a large concentration difference between the inside and outside of the coating during charging. This concentration polarization negatively impacts rate performance and lifespan. c With t Al A ratio of 2.5-4.5 ensures the proportion of active materials while avoiding conduction imbalance, achieving matching of electron and ion conduction rates and laying the foundation for high magnification.
[0025] In this invention, the compaction density of the positive electrode coating is represented by PDc. PDc is related to ρ c The ratio is 0.55-0.65, when PDc and ρ c When the ratio of PDc to ρ is less than 0.55, the coating is loose, the bonding force between active material particles is weak, the compaction density is low, and the coating cohesion and adhesion are poor. This makes it prone to powder shedding during cyclic charging and discharging, resulting in electrode structure damage and affecting cycle life. cIf the ratio of PDc to ρ is greater than 0.65, the coating is too dense, making it difficult for the electrolyte to penetrate into the coating, narrowing the ion transport channels, increasing ion transport impedance, and reducing the charge / discharge capacity at high rates; c A ratio of 0.55-0.65 can balance structural stability and electrolyte wettability, preventing powder shedding while promoting ion transport, ensuring cycle life without sacrificing rate capability.
[0026] In this invention, the conductive agent in the positive electrode active material layer accounts for 5%-10% of the total mass of the positive electrode active material layer. When the proportion is less than 5%, the conductive agent content is low, and the conductive agent cannot form a continuous electronic pathway, resulting in a large electrode resistance and reduced electron conduction rate, affecting rate performance. When the proportion is greater than 10%, the conductive agent occupies space in the active material, leading to a decrease in energy density. The 5%-10% mass of the conductive agent in the positive electrode active material layer achieves a balance between electron conduction efficiency, energy density, and cost, ensuring rapid electron transport at high rates.
[0027] In this invention, the total double-sided coating thickness of the negative electrode active material layer after roll forming is represented by ta, and the thickness of the negative electrode current collector is represented by t. Cu This indicates that ta and t Cu The ratio is 4.0-7.5. Because the ion intercalation capacity and conductivity of the negative electrode active material differ from those of the positive electrode, a thicker coating is needed to match the positive electrode reaction; therefore, the ratio range is higher than that of the positive electrode. If the ratio is less than 4.0, the proportion of negative electrode current collector is high, and the active material is insufficient, which can easily lead to the incomplete containment of lithium ions generated by the positive electrode by the negative electrode, causing lithium plating. If the ratio is greater than 7.5, the coating is too thick, the ion migration path within the negative electrode is long, polarization is intensified, and the 5C discharge rate decreases. (ta and t) Cu The ratio of 4.0-7.5 is adapted to the core function of the negative electrode to accommodate lithium ions, while avoiding conduction imbalance and working in synergy with the positive electrode parameters to achieve matching of the positive and negative electrode reaction rates.
[0028] The compaction density of the negative electrode coating is expressed as PDa, and the ratio of PDa to ρa is 0.60-0.72. The layered structure of the negative electrode material is more prone to expansion, so the ratio range is slightly higher than that of the positive electrode, balancing expansion resistance and wettability.
[0029] If the ratio of PDa to ρa is less than 0.60, the coating is too loose, and the graphite particles are prone to falling off due to expansion during charging and discharging, resulting in a shortened cycle life. If the ratio is greater than 0.72, the coating is too dense, making it difficult for the electrolyte to wet, increasing the ion transport impedance, and reducing the 5C discharge rate. A PDa to ρa ratio of 0.60-0.72 can prevent the negative electrode from shedding powder and ensure that the electrolyte can penetrate into the graphite layers, ensuring that lithium ions can be quickly inserted or extracted.
[0030] In this invention, the mass ratio of the conductive agent in the negative electrode active material layer to the total mass of the negative electrode active material layer is 2%-5%. If the ratio is less than 2%, the conductive agent content is low, the electrode resistance is high, and the electron conduction rate is reduced, affecting the rate performance. If the ratio is higher than 5%, the conductive agent content is high, the conductive agent occupies the graphite space, the energy density is reduced, and there is no additional gain. The ratio of the conductive agent in the negative electrode active material layer to the total mass of the negative electrode active material layer is 2%-5%, which can achieve efficient electron conduction with the minimum amount of conductive agent, while taking into account the energy density.
[0031] In this invention, the ratio of the theoretical capacity of the positive electrode to the theoretical capacity of the negative electrode is expressed as the NP ratio, which is 1.1-1.2. If the NP ratio is less than 1.1, the theoretical capacity of the negative electrode is insufficient. During high-rate charging, lithium ions cannot embed into the graphite in time, resulting in the deposition of metallic lithium on the negative electrode surface. Lithium dendrites may pierce the separator, causing a short circuit and damaging the SEI film. The retention rate after 10,000 cycles may be less than 60%. If the NP ratio is higher than 1.2, it will reduce the single-cell energy density. An NP ratio of 1.1-1.2 provides redundancy for lithium ion capacity in the negative electrode, fundamentally avoiding the risk of lithium deposition, while not wasting the positive electrode capacity, achieving a balance between safety and energy density.
[0032] In a preferred embodiment of the present invention, the active material of the positive electrode active material layer includes one or more of ternary materials, lithium iron phosphate, or lithium cobalt oxide; the active material of the negative electrode active material layer includes one or more of graphite, hard carbon, or soft carbon.
[0033] In this invention, the active material of the positive electrode active material layer is, for example, a ternary material, lithium iron phosphate, lithium cobalt oxide, a ternary material and lithium iron phosphate, a ternary material and lithium cobalt oxide, lithium iron phosphate and lithium cobalt oxide, or a mixture of ternary materials, lithium iron phosphate and lithium cobalt oxide; the active material of the negative electrode active material layer is, for example, graphite, hard carbon, soft carbon, graphite and hard carbon, graphite and soft carbon, hard carbon and soft carbon, or a mixture of graphite, hard carbon and soft carbon.
[0034] In a preferred embodiment of the present invention, the separator membrane comprises one or more of polypropylene, polyethylene, polyethylene / polypropylene copolymer, or cellulose.
[0035] The thickness of the isolation membrane is 20-40 μm; The ratio of the porosity to the thickness of the isolation membrane is 0.02-0.022.
[0036] In this invention, the separator is, for example, polypropylene, polyethylene, polyethylene / polypropylene copolymer, cellulose, polypropylene and polyethylene, polypropylene and polyethylene / polypropylene copolymer, polypropylene and cellulose, polyethylene and polyethylene / polypropylene copolymer, polyethylene and cellulose, polyethylene / polypropylene copolymer and cellulose, polypropylene, polyethylene and polyethylene / polypropylene copolymer, polypropylene, polyethylene and cellulose, polypropylene, polyethylene / polypropylene copolymer and cellulose, polyethylene, polyethylene / polypropylene copolymer and cellulose, or polypropylene, polyethylene, polyethylene / polypropylene copolymer and cellulose.
[0037] In this invention, the thickness of the separator directly affects the mechanical strength and ion transport distance. If the separator thickness is less than 20 μm, the mechanical strength is insufficient, and it is easily punctured by burrs and particles on the positive / negative electrode sheets, leading to direct contact and short circuit between the positive and negative electrodes, causing safety hazards such as fire. At the same time, an excessively thin membrane is easily damaged during the stacking and packaging processes, significantly reducing the production yield. If the separator thickness is greater than 40 μm, lithium ions need to pass through a thicker separator to migrate between the positive and negative electrodes, increasing the ion transport distance and increasing the transport impedance from <10Ω to >15Ω. At high rates, the ions cannot keep up with the reaction rate, resulting in reduced discharge capacity and impaired rate performance. A separator thickness of 20-40μm ensures sufficient mechanical strength to resist electrode burrs and process damage, prevent short circuits, and control the ion transport distance within a reasonable range.
[0038] The porosity of a separator membrane is the ratio of the total volume of all interconnected and closed pores within the membrane to the total volume of the entire separator membrane (including pore volume and the solid matrix volume) under standard environmental conditions (temperature 25℃±2℃, relative humidity 45%±5%, standard atmospheric pressure 101.325kPa). The ratio of membrane porosity to thickness is a key indicator of the synergistic effect of electrolyte residue, membrane strength, and ion transport impedance. Essentially, this ratio reflects how many effective ion channels a unit thickness of separator membrane can provide.
[0039] If the ratio of membrane porosity to thickness is less than 0.02, ion transport and electrolyte residue will be insufficient. If the porosity is too low, the amount of electrolyte residue will be small, lithium ions will lack a transport medium, ion transport impedance will increase sharply, and the 5C discharge rate will decrease. If the thickness is too large, the electrolyte will easily dry out during long-term cycling, further shortening the lifespan and failing to meet the requirements for long lifespan.
[0040] If the ratio of membrane porosity to thickness is greater than 0.022, the membrane strength is insufficient, increasing safety risks. If the porosity is too high, the solid portion of the membrane is low, resulting in a significant decrease in mechanical strength. It is easily punctured by electrode burrs or damaged by cell expansion during cycling, leading to short circuits. If the thickness is too thin, the 5C charge ratio and the retention rate after 10,000 cycles both decrease, resulting in both safety and performance losses.
[0041] When the ratio of membrane porosity to thickness is 0.02-0.022, the electrolyte can fully fill the pores, resulting in low ion transport impedance and a 5C discharge rate ≥85%. The membrane strength meets the standard, with no risk of short circuit. During long-term cycling, the electrolyte is not prone to drying out, and the lifespan is stable.
[0042] The ratio of membrane porosity to thickness is 0.02-0.022, which matches the thickness of 20-40μm. Regardless of whether the thickness is 20μm, 30μm or 40μm, the porosity can be adjusted to ensure sufficient ion channels per unit thickness and no compromise on membrane strength, achieving a synergy of rate capability, lifespan and safety.
[0043] A thickness of 20-40μm ensures reasonable membrane strength and ion transport distance; a ratio of 0.02-0.022, through the combination of porosity and thickness, further optimizes electrolyte residue and ion transport efficiency, avoiding existing technical defects such as high impedance of thick films, poor film strength, easy breakage of porous films, and poor mass transfer of few-pore films, ultimately achieving the requirement that the separator membrane can prevent short circuits, achieve high rate of operation, and have a long life.
[0044] In a preferred embodiment of the present invention, the areal density of the positive electrode active material layer is 8-12 mg / cm³. 2 The areal density of the negative electrode active material layer on one side is 3.5-4.5 mg / cm³. 2 .
[0045] In this invention, if the areal density of the positive electrode active material layer is less than 8 mg / cm³, then... 2 Existing coating equipment is prone to tape breakage and uneven coating, resulting in a sharp drop in production yield. Furthermore, insufficient active material can cause the energy density to fall below 95Wh / kg, rendering it impractical; if it exceeds 12mg / cm³... 2 Excessive coating thickness leads to a longer lithium-ion migration path, resulting in a lower 5C charge ratio and discharge rate, and a decrease in high-rate performance.
[0046] If the areal density of the negative electrode active material layer on one side is less than 3.5 mg / cm³ 2 The coating is prone to leakage, and insufficient negative electrode active material can lead to incomplete lithium ion containment, so even if the NP ratio is compliant, there is still a risk of lithium plating; if it exceeds 4.5 mg / cm³... 2 Excessive coating thickness exacerbates volume expansion during charging and discharging, leading to coating peeling, a decrease in 5C discharge rate, and a retention rate of only 60% after 10,000 cycles. A coating thickness of 3.5-4.5 mg / cm² ensures coating stability, provides ample space for lithium-ion storage, and avoids impedance and lifespan issues associated with excessive coating thickness.
[0047] Positive electrode 8-12 mg / cm 2 With the negative electrode 3.5-4.5 mg / cm 2This matching approach avoids the dual drawbacks of thin-area density (low energy, difficult to manufacture) and thick-area density (high impedance, low rate capability), while also synergizing with parameters such as the ratio of positive and negative electrode coating thickness and compaction density to ensure matching of lithium-ion transport rates between the positive and negative electrodes. Ultimately, it achieves a balance between scalable production of energy storage cells, high energy density, and high rate capability with long lifespan, perfectly meeting the needs of scenarios such as power frequency regulation and regenerative braking.
[0048] In a preferred embodiment of the present invention, the conductive agent includes one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, or porous carbon.
[0049] In this invention, the conductive agent is, for example, conductive carbon black, conductive graphite, graphene, carbon nanotubes, porous carbon, conductive carbon black and conductive graphite, conductive carbon black and graphene, conductive carbon black and carbon nanotubes, conductive carbon black and porous carbon, conductive graphite and graphene, conductive graphite and carbon nanotubes, and conductive graphite and porous carbon. Graphene and carbon nanotubes, graphene and porous carbon, carbon nanotubes and porous carbon, conductive carbon black, conductive graphite and graphene, conductive carbon black, conductive graphite and carbon nanotubes, conductive carbon black, conductive graphite and porous carbon. Conductive carbon black, graphene and carbon nanotubes; conductive carbon black, graphene and porous carbon; conductive carbon black, carbon nanotubes and porous carbon; conductive graphite, graphene and carbon nanotubes; conductive graphite, graphene and porous carbon; conductive graphite, carbon nanotubes and porous carbon; graphene, carbon nanotubes and porous carbon; conductive carbon black, conductive graphite, graphene and carbon nanotubes; conductive carbon black, conductive graphite, graphene and porous carbon; conductive carbon black, conductive graphite, carbon nanotubes and porous carbon; conductive carbon black, graphene, carbon nanotubes and porous carbon; or, a combination of conductive carbon black, conductive graphite, graphene, carbon nanotubes and porous carbon.
[0050] In a preferred embodiment of the present invention, the positive current collector includes one or more of conventional aluminum foil, carbon-coated aluminum foil, or porous aluminum foil; the negative current collector includes one or more of bare copper foil, carbon-coated copper foil, or porous copper foil.
[0051] In this invention, the positive current collector is, for example, conventional aluminum foil, carbon-coated aluminum foil, porous aluminum foil, conventional aluminum foil and carbon-coated aluminum foil, conventional aluminum foil and porous aluminum foil, carbon-coated aluminum foil and porous aluminum foil, or a combination of conventional aluminum foil, carbon-coated aluminum foil and porous aluminum foil. The negative current collector is, for example, bright copper foil, carbon-coated copper foil, porous copper foil, bright copper foil and carbon-coated copper foil, bright copper foil and porous copper foil, carbon-coated copper foil and porous copper foil, or a combination of bright copper foil, carbon-coated copper foil and porous copper foil.
[0052] In a preferred embodiment of the present invention, the electrolyte includes a solvent, an additive, and an electrolyte; The solvent includes one or more of methyl ethyl carbonate, diethyl carbonate, ethylene carbonate, ethyl acetate, propyl acetate, or ethyl propionate. Electrolyte additives include one or more of vinylene carbonate, fluoroethylene carbonate, or 1,3-propane sulpholactone. The amount of electrolyte additive added shall not exceed 2.5% of the total mass of the electrolyte; The electrolyte is lithium hexafluorophosphate, and the concentration of lithium hexafluorophosphate is 1-1.2 mol / L.
[0053] In this invention, the solvent is, for example, methyl ethyl carbonate, diethyl carbonate, ethylene carbonate, ethyl acetate, propyl acetate, ethyl propionate, ethylene carbonate and methyl ethyl carbonate, ethylene carbonate and diethyl carbonate, methyl ethyl carbonate and diethyl carbonate, ethylene carbonate, methyl ethyl carbonate and diethyl carbonate, ethylene carbonate, methyl ethyl carbonate and ethyl acetate, or a combination of ethylene carbonate, diethyl carbonate and propyl acetate.
[0054] In this invention, additives optimize electrolyte performance. If the additive content exceeds 2.5%, it is prone to excessive deposition on the electrode surface, forming an overly thick passivation layer, which increases ion transport impedance and consequently reduces high-rate charge-discharge performance. Simultaneously, excessive additives may react with the electrolyte or solvent, consuming effective components, shortening electrolyte lifespan, and accelerating capacity decay in the later stages of cycling. Controlling the additive content to ≤2.5% allows it to fulfill its functionality while avoiding side effects.
[0055] In this invention, lithium hexafluorophosphate (LiPF6) is the conductive salt of the electrolyte, and its concentration directly affects the ionic conductivity and electrolyte stability. If the concentration of lithium hexafluorophosphate is less than 1 mol / L, the concentration of lithium ions dissociated from the electrolyte is insufficient, resulting in decreased ionic conductivity. At high rates, the lithium ion transport supply cannot meet the demand, leading to a decrease in charge and discharge capacity. If the concentration of lithium hexafluorophosphate is greater than 1.2 mol / L, the excessively high concentration will cause a sharp increase in electrolyte viscosity, increasing the resistance to lithium ion migration and thus reducing ion transport efficiency. At the same time, excess lithium hexafluorophosphate is prone to hydrolysis, generating corrosive substances such as HF, which exacerbates the dissolution of electrode materials and shortens cycle life.
[0056] When the lithium hexafluorophosphate concentration is in the range of 1-1.2 mol / L, the electrolyte ionic conductivity reaches 8-12 mS / cm, which can ensure a sufficient supply of lithium ions and control the electrolyte viscosity in a low resistance range. In synergy with the solvent system, it can achieve efficient ion transport at high rates, while reducing side reactions and ensuring long-term cycle stability.
[0057] According to a second aspect of the present invention, a battery device is provided, comprising a high-rate, long-life energy storage cell as described above, wherein the battery device is at least one of a battery module, a battery pack, or an energy storage battery.
[0058] According to a third aspect of the present invention, an electrical device is provided, characterized in that it includes a battery device as described above.
[0059] According to a fourth aspect of the present invention, an energy storage device is provided, comprising a battery device as described above, the battery device being used to store electrical energy.
[0060] Example The preparation method for high-rate, long-life energy storage cells is as follows: 1. Preparation of positive electrode sheet Weigh out NCM523 material, conductive carbon black and porous carbon (mass ratio 1:1), and polyvinylidene fluoride according to the design ratio, use N-methylpyrrolidone (NMP) as solvent, mix them evenly in a planetary mixer to prepare a positive electrode slurry with a solid content of 50%-70%. The slurry is evenly coated on the surface of the aluminum current collector with a thickness of 15-30um, and the surface density of the coating on one side is controlled to the design value. After coating, vacuum dry at 80-120℃ for 12-24h to remove solvent; then roll press to control the thickness ratio of the positive electrode coating to the aluminum current collector (tc / tAl) and the ratio of the positive electrode compaction density to the true density (PDc / ρc) to the design values. Cut it into 100mm×100mm pieces to obtain the positive electrode sheet.
[0061] 2. Preparation of negative electrode sheet Weigh out graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber according to the design ratio, use deionized water as solvent, and stir to prepare a negative electrode slurry with a solid content of 40%-60%. The slurry is uniformly coated on the surface of the copper current collector with a thickness of 8-15 μm, and the surface density of the coating on one side is controlled to the design value. After coating, vacuum dry at 60-100℃ for 12-24h, then roll press, controlling the thickness ratio of negative electrode coating to copper current collector (ta / tCu) and the ratio of negative electrode compaction density to true density (PDa / ρa) to the design values. Cut it into 104mm*104mm pieces to obtain the negative electrode sheet.
[0062] 3. Pretreatment of the separator membrane A cellulose membrane was selected, and its thickness was controlled to be 20-40 μm. The ratio of porosity to thickness was the design value. The separating membrane is vacuum dried at 80-100℃ for 12 hours to remove moisture and is then ready for use.
[0063] 4. Electrolyte preparation In an argon-protected glove box (moisture <10ppm, oxygen <10ppm), the solvents were mixed in a mass ratio of EC:EMC:DEC:EP = 20%:30%:40%:10%; Add lithium hexafluorophosphate (LiPF6) to the solvent and stir until completely dissolved, controlling the electrolyte concentration to 1.1 mol / L; Add 1% DTD, 1% FEC, and 0.5% VC according to the total mass of the electrolyte and continue stirring for 30-60 minutes to obtain a homogeneous electrolyte.
[0064] 5. Cell assembly and activation The positive electrode, separator, and negative electrode are alternately stacked using a lamination process to form a bare cell. The bare core is placed into an aluminum-plastic film shell, vacuum sealed, and the liquid injection port is retained. Inject the prepared electrolyte into the injection port and let it stand for 30-60 minutes to allow the electrolyte to fully wet the electrode and the separator. After sealing the injection port, a formation process is performed, charging at a constant current of 0.1C to 3.65V, and allowing it to stand for 10 minutes to form a stable SEI film; The final energy storage cell was obtained by performing a capacity grading process of 0.5C charge and discharge three times and recording the capacity.
[0065] The differences between the various embodiments and comparative examples are only reflected in the numerical adjustment of the design parameters. The preparation process, equipment, and basic process conditions such as drying temperature and stirring time are kept consistent.
[0066] The parameter settings for the examples and comparative examples are shown in Table 1. Performance tests were conducted on the high-rate, long-life energy storage cells prepared in the examples and comparative examples. The test results for their energy density, 5C constant current charge ratio, 5C discharge rate, and 5C cycle life of 10,000 cycles are shown in Table 2. The ambient temperature for the following tests was 25℃±2℃. The energy density was calculated as follows: the battery was charged at a constant current of 1C to its full voltage, then charged at a constant voltage to 0.05C, and then discharged at a 1C rate to its minimum voltage. The energy data during the charging and discharging process was recorded using a charge / discharge tester, and the energy density was obtained by dividing the battery energy density by the battery weight.
[0067] The 5C constant current charge ratio test method is as follows: the battery is charged to full voltage with a constant current of 5C rate, and then charged to 0.05C with constant voltage. The constant current and constant voltage charging capacity of the battery are recorded using a charge and discharge tester. The constant current charge ratio = constant current charging capacity / (constant current charging capacity + constant voltage charging capacity). The cycle life test is as follows: the battery is charged to full voltage at a constant current of 5C, and then discharged to the minimum voltage at a constant current of 5C. The above process is repeated 10,000 times, and the capacity of each charge and discharge is recorded. The capacity retention rate of the cell is the percentage of the discharge capacity to the initial capacity.
[0068] Table 1 Parameter settings for the examples and comparative examples
[0069] Table 2 Performance Test Results
[0070] Energy density is mainly affected by the areal density of the positive and negative electrodes and the content of the conductive agent. The areal densities of the positive and negative electrodes are respectively between 8-12 mg / cm³. 2 3.5-4.5 mg / cm 2 Within a certain range, the closer the areal density is to the upper limit of that range, the higher the proportion of active material and the better the energy density performance. For example, the areal densities of the positive and negative electrodes in Example 6 reached the upper limit of this range, and their energy density reached 115Wh / kg, which is the highest among all cases. If the areal density is lower than the lower limit of this range, such as the positive electrode areal density of 7mg / cm³ in Comparative Example 4, the energy density is lower. 2 Negative electrode surface density 3mg / cm³ 2 The energy density is only 90Wh / kg, and the production yield is also low. If the content of conductive agent exceeds the limit, such as the positive electrode conductive agent content of 12% and the negative electrode conductive agent content of 6% in Comparative Example 6, it will squeeze the space of active material, ultimately causing the energy density to drop to 102Wh / kg.
[0071] The 5C rate performance depends on the ion and electron conduction efficiency. When the coating thickness ratio is close to the lower limit of the specified range, such as the ratio of the total coating thickness to the current collector thickness of the positive electrode double-sided in Example 2 (2.51) and the ratio of the total coating thickness to the current collector thickness of the negative electrode double-sided in Example 2 (4.01), the ion migration path is shorter, the 5C charge ratio is not less than 90%, and the 5C discharge rate is not less than 92%, which is the best among all cases. If the coating thickness ratio exceeds the upper limit of the specified range, such as the ratio of the total coating thickness to the current collector thickness of the positive electrode double-sided in Comparative Example 1 (6.4) and the ratio of the total coating thickness to the current collector thickness of the negative electrode double-sided in Example 1, the ion migration path is shorter, the 5C charge ratio is not less than 90%, and the 5C discharge rate is not less than 92%, which is the best among all cases. If the current collector thickness ratio is 9.9, or the compaction density ratio exceeds the upper limit of the specified range (e.g., the ratio of the compaction density of the positive electrode coating to the true density of the active material in Comparative Example 3 is 73.6%, and the ratio of the compaction density of the negative electrode coating to the true density of the active material is 77.5%), or if the conductive agent content is insufficient (e.g., the content of the positive electrode conductive agent is 3%, and the content of the negative electrode conductive agent is 1%), it will lead to excessively long ion paths, insufficient electrolyte wetting, and broken electronic pathways, thereby reducing the 5C charge ratio to the 62%-80% range and the 5C discharge rate to the 71%-82% range.
[0072] The 5C cycle life is controlled by the stability of the electrode structure and the risk of lithium plating. In the examples, the compaction density ratio meets the requirements, which can ensure the electrode structure's resistance to charge and discharge expansion. The NP ratio is in the range of 1.1-1.2, which can effectively avoid the lithium plating problem. Therefore, the cycle retention rate is not less than 85%. However, the NP ratio of Comparative Example 4 is 1.05, which is lower than the limit. It will lead to lithium plating due to insufficient negative electrode capacity, which will damage the SEI film. The coating thickness ratio of Comparative Example 1 exceeds the upper limit of the limit, which is prone to coating expansion and damage. The separator parameters of Comparative Example 3 are out of range, resulting in insufficient film strength. All these situations cause the cycle retention rate to drop below 70%. Among them, the cycle retention rate of Comparative Example 3 is only 50%, which is the worst among all cases. This fully highlights the key significance of structural stability and lithium plating-free state for the long life of energy storage cells.
Claims
1. A high-rate, long-life energy storage cell, characterized in that, Including electrode components and electrolyte; The electrode assembly includes a positive electrode, a separator, and a negative electrode stacked sequentially. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector; The following structural parameters after rolling are controlled collaboratively: The ratio of the theoretical capacity of the positive electrode to the theoretical capacity of the negative electrode is 1.1-1.2; The parameters of the positive electrode active material layer after rolling meet the following: The ratio of the total thickness of the double-sided coating of the positive electrode active material layer to the thickness of the positive electrode current collector is 2.5-4.5; The ratio of the compaction density of the coating of the positive electrode active material layer to the true density of the active material in the positive electrode active material layer is 0.55-0.65; The mass of the conductive agent in the positive electrode active material layer accounts for 5%-10% of the total mass of the positive electrode active material layer; The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector; And the following structural parameters after rolling are controlled in a coordinated manner: The ratio of the total thickness of the double-sided coating of the negative electrode active material layer to the thickness of the negative electrode current collector is 4.0-7.5; The ratio of the compaction density of the coating of the negative electrode active material layer to the true density of the active material in the negative electrode active material layer is 0.60-0.72; The mass ratio of the conductive agent in the negative electrode active material layer to the total mass of the negative electrode active material layer is 2%-5%; This ensures that the energy storage cell retains ≥85% of its capacity after 10,000 cycles at 25°C and 5C rate. The areal density of the positive electrode active material layer is 8-12 mg / cm³. 2 The areal density of the negative electrode active material layer on one side is 3.5-4.5 mg / cm³. 2 .
2. The high-rate, long-life energy storage cell as described in claim 1, characterized in that, The active material of the positive electrode active material layer includes one or more of ternary materials, lithium iron phosphate, or lithium cobalt oxide. The active material of the negative electrode active material layer includes one or more of graphite, hard carbon, or soft carbon.
3. The high-rate, long-life energy storage cell as described in claim 1, characterized in that, The separator membrane comprises one or more of polypropylene, polyethylene, polyethylene / polypropylene copolymer, or cellulose; The thickness of the isolation membrane is 20-40 μm; The ratio of the porosity to the thickness of the isolation membrane is 0.02-0.
022.
4. The high-rate, long-life energy storage cell as described in claim 1, characterized in that, The conductive agent includes one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, or porous carbon.
5. The high-rate, long-life energy storage cell as described in claim 1, characterized in that, The positive current collector includes one or more of conventional aluminum foil, carbon-coated aluminum foil, or porous aluminum foil; The negative electrode current collector includes one or more of the following: plain copper foil, carbon-coated copper foil, or porous copper foil.
6. The high-rate, long-life energy storage cell as described in claim 1, characterized in that, The electrolyte includes a solvent, additives, and an electrolyte; The solvent includes one or more of methyl ethyl carbonate, diethyl carbonate, ethylene carbonate, ethyl acetate, propyl acetate, or ethyl propionate. Electrolyte additives include one or more of vinylene carbonate, fluoroethylene carbonate, or 1,3-propane sulpholactone. The amount of electrolyte additive added shall not exceed 2.5% of the total mass of the electrolyte; The electrolyte is lithium hexafluorophosphate, and the concentration of lithium hexafluorophosphate is 1-1.2 mol / L.
7. A battery device, characterized in that, The battery device includes any one of the high-rate, long-life energy storage cells according to claims 1-6, wherein the battery device is at least one of a battery module, a battery pack, or an energy storage battery.
8. An electrical device, characterized in that, Includes the battery device as described in claim 7.
9. An energy storage device, characterized in that, Includes the battery device of claim 7, the battery device being used to store electrical energy.
Citation Information
Patent Citations
Lithium-iron battery diaphragm and lithium-iron diaphragm
CN109037559A
Electrochemical device and electronic device
CN114665066A
Electrode plate and electrochemical device
CN115394954A
Electrochemical device and electronic device
CN115472776A
Lithium manganese iron phosphate battery with ultrahigh power, high specific energy, wide temperature range and high safety and preparation method thereof
CN119725675A